2011
DOI: 10.1039/c1dt10312a
|View full text |Cite
|
Sign up to set email alerts
|

Spin crossover and polymorphism in a family of 1,2-bis(4-pyridyl)ethene-bridged binuclear iron(ii) complexes. A key role of structural distortions

Abstract: Two polymorphic modifications 1 and 3 of binuclear compound [{Fe(dpia)(NCS)(2)}(2)(bpe)] and pseudo-polymorphic modification [{Fe(dpia)(NCS)(2)}(2)(bpe)]·2CH(3)OH (2), where dpia = di-(2-picolyl)amine, bpe = 1,2-bis(4-pyridyl)ethene, were synthesized, and their structures, magnetic properties, and Mössbauer spectra were studied. Variable-temperature magnetic susceptibility measurements of three binuclear compounds show different types of magnetic behaviour. The complex 1 exhibits a gradual two-step spin crosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…In addition to recently reported binuclear SCO complexes with the bis-monodentate 4,4Ј-bipyridine (4,4Ј-bpy) [15] and 1,2-bis(4-pyridyl) ethene (bpe) [18] bridging units, two new binuclear SCO compounds [{Fe(dpia)(NCS) 2 } 2 (bpac)] (1) and [{Fe(dpia)-(NCS) 2 } 2 (bpac)]·2CH 3 OH (2) [dpia = bis(2-picolyl)amine] with the 1,2-bis(4-pyridyl)ethyne (bpac) spacer ligand have been isolated. The new complexes show different types of SCO: 1 exhibits a two-step spin change, whereas 2 displays a relatively abrupt full one-step spin transition.…”
Section: Step [Hs-hs] ↔ [Ls-ls] Two-step With a Plateau [Hs-hs] ↔ [Hmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to recently reported binuclear SCO complexes with the bis-monodentate 4,4Ј-bipyridine (4,4Ј-bpy) [15] and 1,2-bis(4-pyridyl) ethene (bpe) [18] bridging units, two new binuclear SCO compounds [{Fe(dpia)(NCS) 2 } 2 (bpac)] (1) and [{Fe(dpia)-(NCS) 2 } 2 (bpac)]·2CH 3 OH (2) [dpia = bis(2-picolyl)amine] with the 1,2-bis(4-pyridyl)ethyne (bpac) spacer ligand have been isolated. The new complexes show different types of SCO: 1 exhibits a two-step spin change, whereas 2 displays a relatively abrupt full one-step spin transition.…”
Section: Step [Hs-hs] ↔ [Ls-ls] Two-step With a Plateau [Hs-hs] ↔ [Hmentioning
confidence: 98%
“…[15] It has been concluded that the three types of SCO in binuclear compounds are conditioned by the degree of distortion of the [FeN 6 ] octahedral geometry in different spin-state pairs, which is caused by both crystal packing and strain effects that arise from terminal and/or bridging ligands. [18] A full one-step SCO can be observed for weakly constrained [HS-HS] species and for systems involving a sterically constrained zone, common to both iron centers, that arises from a bridging ligand. The stabilization of the mixed [HS-LS] complex at the plateau temperature for the two-step or partial (50 %) SCO results from an additional distortion of the HS site in the mixed pair.…”
Section: Step [Hs-hs] ↔ [Ls-ls] Two-step With a Plateau [Hs-hs] ↔ [Hmentioning
confidence: 98%
See 1 more Smart Citation
“…[25][26][27] It has been shown that serious differences in the degree of distortion of FeN 6 chromophore geometries can lead to various spin-crossover behaviors: One-step, twostep, or incomplete (50 %) transitions. On the other hand, our investigations of 3D network [Fe(qbtr) 3 ](ClO 4 ) 2 containing flexible ligand bridges did not reveal any influence of conformational alterations on the FeN 6 geometry.…”
Section: Resultsmentioning
confidence: 99%
“…[19] It is also assumed that in dinuclear complexes containing crystallographically unique iron(II) ions, intermolecular interactions influence spin-crossover properties leading to the occurrence of an intermediate phase comprising LS-HS or 50 % HS-HS and 50 % LS-LS pairs. [24] Investigations of dinuclear complexes based on 1,2-bis(4-pyridyl)ethane, [25] bis(2-picolyl)amine, [26] and 1,2-bis(4-pyridyl)ethyne [27] showed that a degree of distortion in the [FeN 6 ] chromo-phore caused by ligand strain and packing effects is responsible for spin-crossover (SCO) behavior. It is worth noting that the number of steps in the spin-transition curve does not necessarily match the number of crystallographically distinct iron(II) ions in a crystal lattice.…”
Section: Introductionmentioning
confidence: 99%